STRANGE BARYON PRODUCTION IN Z-HADRONIC DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Alvsvaag, S; Amaldi, U; Amato, S; et al. (1995)
A study of the production of strange octet and decuplet baryons in hadronic decays of the Z recorded by the DELPHI detector at LEP is presented. This includes the first measurement of the ∑± average multiplicity. The total and differential cross sections, the event topology and the baryon-antibaryon correlations are compared with current hadronization models. © 1995 Springer-Verlag.